Psychiatric comorbidity in a cohort of heroin and amphetamine users in Perth Western Australia - Bartu, Anne; Codde, James (Informa Healthcare, 2003)
Aims: To determine if amphetamine and opioid users attending a drug treatment service were more likely to be admitted to psychiatric services than users not receiving treatment.Method: Client records form Next Step Specialist Drug and Alcohol Services (Next Step) and the Community Based Methadone Program (CBMP) were linked to mental health and hospital morbidity data files using probabilistic matching.Participants: The sample comprised 4280 drug users (2887 opioid users, 1393 amphetamine users). Of these, 928 received methadone at either Next Step or the CBMP, 541 attended counselling or a support group at Next Step, and 2811 did not receive treatment from Next Step or the CBMP during the study.Findings: Irrespective of treatment received, clients who had recently withdrawn from treatment were at the highest risk of psychiatric admission, experiencing seven times the hazard of admission compared with those who did not access drug treatment. Amphetamine users had at least three times the hazard of psychiactric admission compared with opioid users. Clients with a history of psychiatric admissions had twice the hazard of subsequent admission compared with those with no psychiatric history.Conclusions: Clients presenting at a drug treatment service should be screened for mental health diasgnosis at their initial assessment so that appropriate treatment strategies can be offered to these dually diagnosed clients.